2009
DOI: 10.4318/tjg.2013.0582
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing symptoms after eradication of Helicobacter pylori: Psychiatric disorders may accompany!

Abstract: Background/aims: The precise mechanism of functional dyspepsia is yet to be elucidated. Helicobacter pylori infection and psychi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
0
7
1
Order By: Relevance
“…The prevalence of probable case of depression found among patients with H . pylori infection (11.9%) in this study was lower than the findings of studies conducted in Turkey (24.1%) [ 38 ] and the Kingdom of Bahrain (32.1%) [ 20 ]. The difference may again be related to the tools used to assess depression (PHQ-9 vs Composite International Diagnostic Interview (CIDI) and Hamilton Depression Rating Scale (HDRS)).…”
Section: Discussioncontrasting
confidence: 86%
“…The prevalence of probable case of depression found among patients with H . pylori infection (11.9%) in this study was lower than the findings of studies conducted in Turkey (24.1%) [ 38 ] and the Kingdom of Bahrain (32.1%) [ 20 ]. The difference may again be related to the tools used to assess depression (PHQ-9 vs Composite International Diagnostic Interview (CIDI) and Hamilton Depression Rating Scale (HDRS)).…”
Section: Discussioncontrasting
confidence: 86%
“…They concluded that H. pylori eradication might be the key to success for the treatment of F.D patients and to prevent the development of gastric cancer [34]. Ünal et al enrolled 54 patients with functional dyspepsia and H. pylori infection without knowing their psychiatric illnesses [35]. They found 22 of them to have at least one psychiatric illness; the most common was depression in about 13 patients.…”
Section: Reviewmentioning
confidence: 99%
“…They found 22 of them to have at least one psychiatric illness; the most common was depression in about 13 patients. They concluded that psychiatric illness should be considered for patients who fail the treatment of symptoms after H. pylori eradication, as it will affect their treatment [35]. A prospective study by Kabeer et al to determine the prevalence of H. pylori and depression in patients with functional dyspepsia and to assess the outcome in three months after appropriate intervention enrolled 120 patients with functional dyspepsia, who underwent upper endoscopy to confirm H. pylori infection with either of two tests- the urease test or histopathology [36].…”
Section: Reviewmentioning
confidence: 99%
“…It is also possible that psychiatric disorders in H. pylori-infected subjects result from disease overlap, with comorbidity in 40% of patients with functional dyspepsia, of which depression is the most prevalent (24%) [111] .…”
Section: Disordersmentioning
confidence: 99%
“…Furthermore, additional placebo-controlled trials and a meta-analysis did not show improvement in dyspeptic symptoms with H. pylori eradication [129][130][131] . Discrepancies regarding symptomatic response to H. pylori eradication may relate to commonly occurring comorbid psychiatric disorders, which can affect treatment outcome [111] . H. pylori infection is also considered a cause of visceral hypersensitivity in patients with IBS, as individuals reporting typical abdominal discomfort after rectal barostat testing were more frequently H. pylori positive [42,43] .…”
Section: H Pylori and Visceral Sensitivitymentioning
confidence: 99%